Effect of Selected Plant Protection Chemicals on the Beneficial Microorganisms in Cowpea Rhizosphere - Raji P (Department of Plant Pathology, College of Horticulture, 1995)
A study was conducted at the College of Horticulture, Vellanikkara, during 1992 – 94, on the effect of selected plant protection chemicals on beneficial microorganisms in cowpea rhizosphere. Four fungicides, three insecticides and their combinations were tested in vitro as well as in the field. The tolerance levels of Azospirillum and Bradyrhizobium to different doses of these chemicals were also tested. The fungicide Thiram caused inhibition of Azospirillum in vitro. The adverse effect of Thiram on rhizosphere population of Azospirillum was seen only during initial days after application. The growth performance of cowpea plants were not affected adversely. The fungicides, Carbendazim, Bordeaux mixture and Fytolan and insecticides Carbofuran, Phorate and HCH at their recommended doses did not cause inhibition of Azospirillum in vitro and did not reduce the rhizosphere population of Azospirillum. The growth performance of cowpea plants was also not affected adversely by these fungicides and insecticides. The combinations of insecticides with Thiram caused inhibition of Azospirillum under in vitro conditions and caused reduction in rhizosphere population of the bacteria initially. But no adverse effect on growth of cowpea plant was noticed. Bradyrhizobium was inhibited by the fungicides, Thiram, Bordeaux mixture and Fytolan in vitro. The rhizosphere population of Bradyrhizobium also showed reduction initially. The growth performance of plants was not affected adversely. The number of nodules showed significant reduction. No reduction in nitrogen content was noticed. Carbendazim and insecticides Carbofuran, Phorate and HCH did not show inhibition of Bradyrhizobium in in vitro. The rhizosphere population and growth of cowpea plants were also not affected adversely by these chemicals. Under in vitro conditions the combination of insecticides with Thiram, Bordeaux mixture and Fytolan caused inhibition of Bradyrhizobium. The rhizosphere population showed reduction initially, later on it was increased. The combination of insecticides with Carbendazium did not inhibit the growth of Bradyrhizobium under in vitro conditions and also in the rhizosphere. The treatment combinations did not affect the growth of cowpea plants in the field adversely. The tolerance levels of Azospirillum and Bradyrhizobium to different doses of fungicides and insecticides were also tested. The fungicides Carbendazim, Bordeaux mixture and Fytolan were not inhibitory to Azospirillum, even their highest doses of 0.15, 3.0 and 0.5 per cent respectively. Similarly, the insecticides Carbofuran, phorate and HCH were also not inhibitory to Azospirillum at their highest doses tested. The fungicide Thiram caused inhibition of Azospirillum even at the lowest dose of 0.05 per cent.